2003
DOI: 10.1023/a:1022977002954
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Collection of oocytes from small follicles, especially with a mean diameter less than 10 mm, and in vitro maturation of immature oocytes before fertilization may allow the total number of good quality and transferable embryos to be increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…However, the rate of in vivo– matured oocytes positively correlates with dominant follicle size (dominant follicle ≤10 mm, 6.9%; 10 to 14 mm, 10.6%; >14 mm, 15.1%) ( 233 ). Similarly, Triwitayakorn et al ( 238 ) observed that oocyte recovery rate increased from 57% of follicles <10 mm to 80% of follicles 10 to 14 mm and further to 86% of follicles >14 mm on the day of oocyte retrieval.…”
Section: Endocrine Requirements For Oocyte Maturation and Ovulationmentioning
confidence: 85%
“…However, the rate of in vivo– matured oocytes positively correlates with dominant follicle size (dominant follicle ≤10 mm, 6.9%; 10 to 14 mm, 10.6%; >14 mm, 15.1%) ( 233 ). Similarly, Triwitayakorn et al ( 238 ) observed that oocyte recovery rate increased from 57% of follicles <10 mm to 80% of follicles 10 to 14 mm and further to 86% of follicles >14 mm on the day of oocyte retrieval.…”
Section: Endocrine Requirements For Oocyte Maturation and Ovulationmentioning
confidence: 85%
“…However, the rate of in vivo matured oocytes positively correlated with follicle size (dominant follicle ≤10 mm 6.9%, 10–14 mm 10.6%, >14 mm 15.1%) ( 36 ). Finally, Triwitayakorn et al observed that oocyte recovery rate increased from 57% of follicles < 10 mm to 80% of follicles 10–14 mm and further to 86% of follicles > 14 mm on the day of oocyte retrieval ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“… Increasing n.e. Triwitayakorn 2003 [ 14 ] P 35.9 Long short Only ICSI 991 10-14 Always increasing together with oocyte recovery rate None n.e. none Rosen 2008 [ 19 ] P 34.1 Long shortantag IVF/ICSI 2934 10-13-16-19 IVF: n.e.…”
Section: Methodsmentioning
confidence: 99%